Baclofen Pump Use: Complications After Growth-friendly Instrumentation for Early-onset Scoliosis. Issue 2 (February 2022) - Xu, Amy L.; Marrache, Majd; Hardesty, Christina K.; Groves, Mari L.; Erickson, Mark A.; Murphy, Robert F.; Thompson, George H.; Sponseller, Paul D.
Abstract : Background: Patients with early-onset scoliosis (EOS) and spasticity may receive treatment with an intrathecal baclofen pump. We assessed how baclofen pumps are associated with the odds of complications and secondary interventions after growth-friendly (GF) spine surgery for EOS and analyzed infectious complications within the pump cohort. Methods: Using a prospectively maintained, international multicenter database, we studied patients with neuromuscular EOS with baclofen pumps who underwent GF spine surgery from 2002 through 2019 (n=25). Baclofen pumps were implanted before GF instrumentation in 18 patients, during in 2 patients, and after in 5 patients. Patients with existing pumps at initial GF spine surgery were matched 1:3 with 54 patients (control group) without pumps according to treatment center, year of surgery, diagnosis, surgery type, and preoperative curve magnitude. Univariate analysis and multivariate logistic regression were performed to compare complications and secondary interventions between the 2 cohorts. Results: Patients with baclofen pumps had 4.8 times the odds [95% confidence interval (CI): 1.5-16] of experiencing any complication within 1 year after initial GF spine surgery compared with controls. During mean follow-up of 6.9±4.3 years, they had 4.7 times the odds (95% CI: 1.3-16) of deep surgical site infection and 5.6 times the odds (95% CI: 1.2-26) of spinal rod removal after any complication. Differences in rates of mechanical complication, such as rod migration and breakage, were nonsignificant between the 2 groups. For the 9 patients (50%) with pumps who experienced infections, the most common microorganisms were Staphylococcus aureus (4 patients) and Pseudomonas aeruginosa (2). The pump/catheter was revised or removed, in addition to antibiotic therapy or surgical irrigation and debridement, in 2 patients. Conclusions: Among patients with neuromuscular EOS, those with baclofen pumps are much more likely to experience complications within 1 year after GF spine surgery. They are also more likely to have deep surgical site infections, with S. aureus and P. aeruginosa being the most common causative organisms, and to require spinal rod removal. Level of Evidence: Level III—retrospective comparative study.